Design of a heating system for plasma flux simulation - Fallas-Chinchilla, Juan Carlos (2013)
VASIMR® plasma rocket and its possible applications are promoting innovations in the space propulsion area. Ad Astra Rocket Company (VASIMR® designer) constantly needs instruments to evaluate the plasma engine and its components, in order to acquire critical information to warrant a safe operation. This study describes the design and construction of a heating system, to simulate a plasma flux within a ceramic tube. This part of the engine plays a critical role, transporting a gas to ionize at high temperatures, transforming it in plasma for propulsion purposes. In the simulation system, some restrictions were established to match its labor with the tube and its operation conditions in the space.  Making the simulation inside a vacuum chamber to remove the air, and adapting the heaters in a specific position to relate them with the real plasma flux and its behavior, are examples of the simulation requirements. The simulation system was installed in Ad Astra Rocket Company, Costa Rica. It is used to acquire data and study the behavior of the tube under the previously mentioned conditions, and detail a computer-assisted model.